Quantitative evaluation of the surface stability and morphological changes of Cu2O particles - Ferrer, Mateus M.; Fabris, Guilherme S.L. [UNESP]; de Faria, Bruno V. [UNESP]; Martins, João B.L.; Moreira, Mário L.; Sambrano, Julio R. [UNESP] (Elsevier, 2019)
Cu2O low-index surfaces periodic models have been simulated based on density functional theory. The calculated surfaces energies allowed estimating the morphology by means of the Wulff theorem as well as the investigation of possible paths of morphological changes. Therefore, systematic morphology diagrams and change paths according to the energy modulation in relation to the surfaces stabilizations were elaborated. The applicability of this strategy was exemplified by comparing the obtained results with experimental available data from the literature. The morphology diagrams with the quantitative energetic point of view can be used as a guide to support experimental works in order to understand the relation between surface interactions and crystal growth.
Keywords: Crystal growth; Cu2O; DFT; Materials chemistry; Materials science; Morphology; Physical chemistry; Surface; Theoretical chemistry; Wulff